Meperidine-induced reversible retrograde amnesia - DENİZBAŞI ALTINOK, ARZU (ELSEVIER, 2008)
INTRODUCTION: Meperidine is a synthetic opiold analog that is frequently prescribed for acute pain management. Normeperidine, the only active metabolite of meperidine, is neurotoxic and can cause significant central nervous system adverse events. CASE SUMMARY: A 29-year-old woman (height, 170 cm; weight, 85 kg) presented to Marmara University Hospital Emergency Department, Istanbul, Turkey, complaining of low back pain she described as stabbing. Physical examination revealed impaired lower-extremity mobility and normal vital-sign findings. There was no evidence of foot drop, head or other trauma, and systemic physical examination was unremarkable. Other common causes (eg, pyelonephritis, nephrolithiasis, pancreatitis, trauma) of lower back pain were excluded. To achieve analgesia, meperidine 80 mg was administered intravenously in 100 mL of isotonic saline solution for 20 minutes. Within 20 minutes, analgesia was achieved, but the patient developed retrograde amnesia, becoming disoriented to time, location, and persons. Her speech slowed and perceptional changes developed. After the onset of amnesia, a complete physical examination was conducted. It failed to reveal focal neurologic deficit, and laboratory (sodium, potassium, magnesium, phosphorus, serum creatinine, blood urea nitrogen, albumin, billrubin, hemoglobin, and platelet count) and subsequent vital-sign findings (blood pressure, 150/100 mm Hg; heart rate, 100 beats per minute; respiratory rate, 18 breaths per minute; body temperature, 37 degrees C; and pulse oximetry, 99%) were within the normal range. Noncontrast computed tomography did not reveal any abnormality. Initially, the patient's condition was attributed to medication error due to incorrect dosage or infusion rate. Despite a review of medication logs, equipment, and the vital-sign record, the etiology for the phenomenon could not be identified. Meperidine was discontinued and oxygen and intravenous isotonic saline solution were initiated as supportive treatment. Three hours after meperidine administration was discontinued, the amnesia and disorientation spontaneously resolved. CONCLUSION: Meperidine was probably associated with reversible amnesia in this healthy patient after a single therapeutic dose.
Keywords: meperidine; amnesia; opioid analgesic; central nervous system toxicity; PETHIDINE